Health Service Delivery in China : A Literature Review - Eggleston, Karen (World Bank, Washington, DC, 2012)
The authors report the results of a review of the Chinese-language and English-language literatures on service delivery in China, asking how well China's health care providers perform, what determines their performance, and how the government can improve it. They find current performance leaves room for improvement in terms of quality, responsiveness to patients, efficiency, cost escalation, and equity. The literature suggests that these problems will not be solved by simply shifting ownership to the private sector, or by simply encouraging providers-public and private-to compete with one another for individual patients. In contrast, substantial improvements could be (and in some places have already been) made by changing the way providers are paid-shifting away from fee-for-service and the distorted price schedule toward prospective payments. Active purchasing by insurers could further improve outcomes.